UV-Modulated Substrate Rigidity for Multiscale Study of Mechanoresponsive Cellular Behaviors - Sun, Yubing (2012)
Mechanical properties of the extracellular matrix (ECM) have profound effects on cellular functions. Here, we applied novel photosensitive poly-dimethylsiloxane (photoPDMS) chemistry to create photosensitive, biocompatible photoPDMS as a rigidity-tunable material for study of mechanoresponsive cellular behaviors. By modulating the PDMS crosslinker to monomer ratio, UV light exposure time, and post-exposure baking time, we achieved a broad range of bulk Young’s modulus for photoPDMS from 0.027 - 2.48 MPa. Biocompatibility of photoPDMS was assayed and no significant cytotoxic effect was detected as compared to conventional PDMS. We demonstrated that the bulk Young’s modulus of photoPDMS could impact cell morphology, adhesion formation, cytoskeletal structure, and cell proliferation. We further fabricated photoPDMS micropost arrays for multiscale study of mechanoresponsive cellular behaviors. Our results suggested that adherent cells could sense and respond to changes of substrate rigidity at a sub-focal adhesion resolution. Together, we demonstrated the potential of photoPDMS as a photosensitive and rigidity-tunable material for mechanobiology studies.